District nurses' preventive home visits to 75-year-olds: An opportunity to identify factors related to unsafe medication management. Issue 8 (December 2014) - Lagerin, Annica; Carlsson, Axel C.; Nilsson, Gunnar; Westman, Jeanette; Törnkvist, Lena
Aims: To investigate factors related to unsafe medication management among 75-year-olds during preventive home visits, and to describe the interventions district nurses used. Methods : An explorative study. During a 9- to 12-month period, 36 DNs used the Safe Medication Assessment (SMA) tool during preventive home visits to 75-year-olds who used at least one drug ( n =113). Results : One or more factors related to unsafe medication management were identified in 84% of the 75-year-olds. More than 40% used five or more drugs, and 34.5% reported symptoms potentially indicative of adverse effects of their drugs. Nearly 30% had prescribers from more than two medical units, and 7.1% of the older persons were appraised as having reduced cognitive ability. DNs intervened in more than two-thirds of the cases and used a variety of nursing care interventions to improve the safety of medication management. Conclusions : Preventive home visits seem to provide a unique opportunity to promote safe medication management. Several factors related to unsafe medication management were identified, and several different nursing care interventions were carried out to ensure safe medication management. Use of the SMA tool in preventive home visits seems to be advantageous in improving the safety of medication management among older persons.